IMPLEMENTASI PERATURAN DAERAH NOMOR 08 TAHUN 2018 DALAM PENERTIBAN PEDAGANG KAKI LIMA DI KABUPATEN TABALONG (Studi Kasus di Tanjung Expo Center) (JAPB, 2022)
Street vendors are small traders who sell in a public place such as roadsides, parks, overhang shops, markets without a business permit from the government. Because of this, the existence of street vendors is considered very important to be controlled by the local government with the task of assisting Satpol PP in an effort to organize public space, so that it looks more neat and beautiful in accordance with the spatial function of Regency/City cities, one of whose goals is realizing a balance of development, utilization of space or development of areas within the city. The purpose of this study is to find out and analyze the Implementation of Regional Regulation Number 08 of 2018 in Controlling Street Vendors (Case Study of Tanjung Expo Center). The method used in this research is a qualitative approach with descriptive analysis. Data collection techniques used are interviews, observation and documentation. The source of the data in this study was to collect information from 5 informants, namely 1 Head of Satpol PP, 2 members of Satpol PP and 2 street vendors, as well as using interactive model data analysis techniques according to Miles and Huberman. The results of this study indicate that the research and discussion on the Implementation of Regional Regulation Number 08 of 2018 in Controlling Street Vendors (Case Study at Tanjung Expo Center), the authors can conclude that controlling street vendors at Tanjung Expo Center is categorized as implemented. Keywords: Implementation, Controlling, Street Vendors